2012
DOI: 10.1186/1742-4690-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Timing and source of subtype-C HIV-1 superinfection in the newly infected partner of Zambian couples with disparate viruses

Abstract: BackgroundHIV-1 superinfection occurs at varying frequencies in different at risk populations. Though seroincidence is decreased, in the negative partner of HIV-discordant couples after joint testing and counseling in the Zambia Emory HIV Research Project (ZEHRP) cohort, the annual infection rate remains relatively high at 7-8%. Based on sequencing within the gp41 region of each partner's virus, 24% of new infections between 2004 and 2008 were the result of transmission from a non-spousal partner. Since these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 55 publications
0
48
0
Order By: Relevance
“…It is unknown what role HIV SI has on MTCT or sexual transmission, but given the effect it has on viral load, it is possible that SI could temporarily increase the infectiousness of the individual. However, it is difficult to establish the directionality and relationship of SI and transmission events in the setting of sexual transmission [4, 7]. This issue is not relevant in MTCT of HIV, since transmission only occurs vertically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unknown what role HIV SI has on MTCT or sexual transmission, but given the effect it has on viral load, it is possible that SI could temporarily increase the infectiousness of the individual. However, it is difficult to establish the directionality and relationship of SI and transmission events in the setting of sexual transmission [4, 7]. This issue is not relevant in MTCT of HIV, since transmission only occurs vertically.…”
Section: Discussionmentioning
confidence: 99%
“…HIV SI has been demonstrated in multiple cohorts around the world, and occurs at varying rates that can be similar to the corresponding primary HIV incidence rate in the population, although this has not been observed in all studies [2-7]. Rates of HIV SI appear to be higher in populations at increased risk of primary HIV infection, such as female sex-workers [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hypothesis is that superinfection occurs more easily at the early infection stage because of weak immunity. This hypothesis was initially supported by some case reports and cohort studies showing superinfection within one year after initial infection [4,7,12,22,28,39,42,64]. However, later studies showed that the number of superinfection within one year after the initial infection was similar to that after one year of infection [11,19,41,51,74].…”
Section: Superinfection At Different Infection Stagesmentioning
confidence: 91%
“…When individuals are infected with multiple viruses either at the time of initial infection or later, a bulk sequence will not adequately represent all viruses that an individual has acquired or possibly transmitted[31,32]. In these instances SGA and NGS methods can provide a more detailed depiction of intra-host HIV diversity[33-35]. Phylogenies reconstructed from bulk sequences may be subject to greater bias with increasing prevalence of HIV coinfection within a population, though this remains an understudied area in phylogenetics.…”
Section: Viral Sequencing Technologiesmentioning
confidence: 99%